2023
DOI: 10.3390/su15129408
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Online Professional Development Course on Teachers’ Comprehension and Self-Efficacy in Developing Students’ Self-Regulated Learning Skills

Abstract: The ongoing process of digitalisation requires teachers not only to use technologies in their lessons to provide high quality opportunities for learning, but also to learn through this format themselves. In recent years, a new competence-based curriculum has been implemented in Latvia, introducing new content and paying attention to self-regulated learning (SRL) as one of the transversal skills. This requires appropriate teacher professional development (TPD) and the implementation of various digital solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It can be concluded that teachers should be provided with very targeted methodological help and training about how to explicitly apply PS and SRL skills in various school subjects. This conclusion is supported by research that found such interventions to be effective (Benick et al, 2021;Linde et al, 2023).…”
Section: Discussionmentioning
confidence: 77%
“…It can be concluded that teachers should be provided with very targeted methodological help and training about how to explicitly apply PS and SRL skills in various school subjects. This conclusion is supported by research that found such interventions to be effective (Benick et al, 2021;Linde et al, 2023).…”
Section: Discussionmentioning
confidence: 77%
“…Through the utilisation of digital platforms, teachers have unlimited access to the latest educational resources that can enrich and complement 2433 their teaching methods. The ability to participate in online professional training opens up opportunities for teachers to continuously develop their skills, keep up with the latest trends in education and update their teaching strategies according to the latest developments (Linde et al, 2023). In other words, information technology not only provides support in terms of access to resources but also creates an environment where teachers can continuously improve themselves, resulting in a sustainable positive impact on students' learning experience and the overall progress of education.…”
Section: Resultsmentioning
confidence: 99%
“…Teachers could use the affordances/benefits of blended learning (e.g., flexibility) to facilitate the exercise of SRL skills in students; e.g., designing tasks in which students have opportunities for autonomy, decision making, and collaboration [44], or adopting appropriate systems to support SRL in blended learning practices [45]. Professional development can facilitate teachers in acquiring knowledge of and skills in developing students' SRL skills [46]. Sustainable digital pedagogies (including mobile technology-supported pedagogies) and innovative blended practices are recommended.…”
Section: Discussionmentioning
confidence: 99%